Consumer and Manager Preferences for Food Attributes in the Restaurant Industry: The Implications for the Imported Duck Industry in China - Wang, H. Holly; Andrews, Rachel C.; Widmar, Nicole J. Olynk; Ortega, David L (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractUnprecedented economic growth in China has created a new market potential for high-quality foods in the global food industry. This has led several studies to investigate consumer preferences for food safety and quality attributes in the retail market. However, there are limited studies related to the food service sector, specifically to combine these two concepts. Therefore, this study was conducted to investigate these preferences from the perspectives of both the customers and restaurant managers in relation to ducks in the Chinese food service sector. This involved estimating the willingness-to-pays for quality and safety attributes such as branding, premium quality, safety certification, and the biotech country of origin, including the United States, the European Union, and China using regression analysis. The empirical results showed that Chinese consumers and restaurant owners/managers have a similar preference for branded, high quality, and safe domestic products. However, their relative preferences for these attributes are not identical, as indicated by the consumers' highest preference for safety certification, while managers mostly focus on the quality. These findings are expected to provide more information on the market preferences for food produced in emerging Asian economies with special diet cultures and traditions.Keywords: consumer preferences, duck, food safety, food service, manager preferences AbstrakPertumbuhan ekonomi yang belum pernah terjadi sebelumnya di Cina telah menciptakan potensi pasar baru untuk makanan berkualitas tinggi di industri makanan global. Beberapa penelitian telah dilakukan untuk mengetahui preferensi konsumen terhadap keamanan pangan dan atribut kualitas di pasar ritel, tetapi penelitian terkait preferensi tersebut pada sektor jasa pangan belum banyak dilakukan. Oleh karena itu, penelitian ini dilakukan untuk mengetahui preferensi konsumen dan manajer restoran terhadap keamanan pangan dan kualitas bebek pada sektor jasa pangan di Cina. Estimasi menggunakan analisis regresi dilakukan pada kesediaan konsumen dan manajer restoran untuk membayar atribut kualitas dan keamanan pangan, seperti merek, kualitas premium, sertifikasi keamanan, dan negara asal biotech, termasuk Amerika Serikat, Uni Eropa, dan Cina. Hasil empiris menunjukkan bahwa konsumen Cina dan pemilik / manajer restoran memiliki preferensi yang sama terhadap produk dalam negeri yang bermerek, berkualitas tinggi, dan aman, tetapi tingkat preferensi mereka berbeda untuk atribut tersebut. Hal ini ditunjukkan oleh preferensi tertinggi konsumen terdapat pada sertifikasi keamanan, sedangkan manajer sebagian besar fokus pada kualitas. Hasil penelitian ini diharapkan dapat memberikan lebih banyak informasi tentang preferensi pasar untuk makanan yang diproduksi di negara berkembang di Asia dengan budaya dan tradisi diet khusus.Kata kunci: bebek, jasa pangan, keamanan pangan, preferensi konsumen, preferensi manajer